Ritual Ibadah Shalat Rebo Wekasan of the MonthShafar According To Islamic Law - Ahmad Bima Risyta Al Faruq (Yayasan Literasi Kita Indonesia, 2021)
Allah has perfected this Islamic religion and all aspects in it such as maghdhah forms of worship, ghoiru maghdah and so on, no need to be added and subtracted like maghdhah worship, namely prayer, fardu prayer and sunnah, there are standard rules of both time and number. rekaat and its terms and guidelines, but in the modern era there is a prayer ritual performed on the last Rabo month of Shafar with certain rules and conditions, until now there is no basis for the argument. In his book Mujarrobat, Shaykh Ad-Dairobi states,